THE EFFECT OF STORAGE MEDIA (PLASTIC SEED) TO KEEP LONG FRESH CARROT (Daucus carota L.) - Fendriansah - - (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2014)
Carrot is commodity that easy damage at the time of production until it gets to the consumer.  Carrots at room temperature only lasted for four days. Storage technologies are needed by farmers to maintain quality carrots carrots, and can decrease respiration and evaporation of water.  Storage of carrots can be done with a controlled atmosphere, atmospheric termodifkasi, and traditional media storage using plastic seed by providing cooling water outside the storage container.  This research aims to determine the effect of the storage media to keep long fresh carrot (Daucus carota L.). The research method is done by several methods, namely the upper of cooling water outside of storage container in below, equal, and on the surface of plastic seed.  The results showed plastic seed with an average shelf life of 20 days.Keywords: carrots, cooling water, plastic seed and shelf life.